Milker’s Nodule: A Case Report from South India - B, Sruthi; Pavadai, Nithiyaa; M, Trishna Vaishali (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Milker’s nodule is an acute viral infection caused by the bovine strain of the paravaccinia virus transmitted to humans through direct contact with infected cattle. Parapoxvirus infection is usually endemic among livestock herds. It is an occupational dermatosis, and populations at risk include shepherds, butchers, farmers, wool shearers, and veterinarians. We report a 36-year-old female cattle rearer who presented with a few nodular lesions on the hand, along with histopathology and Dermoscopy features. Although it is well documented in endemic livestock regions, reports from South India are limited. Prompt diagnosis of the disease is important for facilitating the implementation of control measures to minimize the losses suffered by farmers.